Application of electrokinetic in controlling heavy metals migration in sand: A feasibility study - Liew, Cindy; Lim, Leonard L. P. (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Uncontrolled migration of heavy metals from human activities in the subsurface can lead to the degradation of environmental quality and potential use of soil and groundwater. This paper studies the feasibility of using electrokinetics in controlling the migration of heavy metals in sand. Copper and iron (initial concentration of 100 mgL-1) are the target heavy metals in this study as they are the most commonly found heavy metals from human activities such as mining and land filling. The performance of electrokinetic in controlling the migration of these heavy metals is tested in a sand tank at combination of water velocity and electrical gradient of 1.3 cm h-1, 0.5 V cm-1 and 0.88 cm h-1, 1 V cm-1, respectively. The formation of gas at electrodes, scouring on carbon anode and corrosion of crocodile clips during experiment (0.88 cm h-1, 1 V cm-1) showed the occurrence of electrokinetics. Further studies need to be conducted to optimize the operating conditions for effective application of electrokinetic in controlling heavy metals migration in sand.